Talking with pediatric patients with overweight or obesity and their parents: self-rated self-efficacy and perceived barriers of Dutch healthcare professionals from seven disciplines - B. van der Voorn; R. Camfferman; J. C. Seidell; J. Halberstadt (BMC, 2022)
Abstract Background Many healthcare professionals (HCPs) feel uncomfortable and incompetent talking about weight with children with overweight and obesity and their parents. To optimally target interventions that can improve obesity care for children, we assessed the self-efficacy (SE) and perceived barriers (PBs) of Dutch HCPs with regard to talking about weight and lifestyle when treating children with overweight or obesity. We also analyzed interdisciplinary differences. Methods A newly developed, practice- and literature-based questionnaire was completed by 578 HCPs from seven disciplines. ANOVA and chi-square tests were used to analyze interdisciplinary differences on SE, PBs, and the effort to discuss weight and lifestyle despite barriers. Regression analyses were used to check whether age, sex or work experience influenced interdisciplinary differences. Results On average, the reported score on SE was 7.2 (SD 1.2; scale 1-10) and the mean number of PBs was 4.0 (SD 2.3). The majority of HCPs (94.6%) reported perceiving one or more barriers (range 0-12 out of 17). HCPs who in most cases perceived too many barriers to discuss weight and lifestyle of the child (9.6%, n = 55) reported a lower SE (mean 6.3) than professionals who were likely to discuss these topics (mean SE 7.3, p < 0.01), despite having a similar number of PBs (mean 4.5 vs 4.0, p > 0.05). In total, 14.2% (n = 82) of HCPs either felt incapable (SE ≤ 5) or reported that in most cases they did not address weight and lifestyle due to PBs. Conclusions Although on average Dutch HCPs rated their self-efficacy as fairly good, for a subgroup major improvements are necessary to lower perceived barriers and improve self-efficacy, in order to improve the quality of care for Dutch children with obesity.